Development of Halal Tourism in West Kalimantan: Analysis Using NVIVO - Nurcholifah, Ita; Barkah; Erna Listiana; Fachrurazi (International Journal of Islamic Business and Economics (IJIBEC), 2023)
This study aims to determine the prospect of halal tourism that must be developed in order to capture opportunities in West Kalimantan. This study uses a qualitative method with a phenomenological approach. Data collection tools by conducting interviews, observations, and documentation by analysis using NVivo 12 Plus. The prospect of halal tourism in West Kalimantan Province is seen from the development of four aspects of development, namely: destinations, marketing, industry, and institutions. The high prospect of halal tourism in West Kalimantan which is so promising, of course, must be the main focus of development as well. Several aspects of the direction of development such as Destinations, Marketing, Industry, and Institutions need to be studied immediately, namely the inclusion of a clearer plan into the Regional Tourism Master Plan (RIPDA) which of course in this case also has an impact on funding, facilities, certification so that halal tourism in West Kalimantan can be realized maximally and develop rapidly. So that in turn it can increase income for the region in order to develop regional development more broadly and evenly to realize the welfare of the community, especially in West Kalimantan Province.